How Do Zoos 'Talk' to Their General Visitors? Do Visitors 'Listen'? A Mixed Method Investigation of the Communication Between Modern Zoos and Their General Visitors. (5th February 2015) - Roe, Katie; McConney, Andrew; Mansfield, Caroline F.
Abstract Modern zoos utilise a variety of education tools for communicating with visitors. Previous research has discussed the benefits of providing multiple education communications, yet little research provides an indication of what communications are being employed within zoos today. This research is a two-phased, mixed-methods investigation into the communication between zoos and their general visitors. Phase 1 involved an online questionnaire to which 176 zoos from 50 countries reported on the types of education communications they typically use for their general visitors. The second phase comprised nine zoo case studies, enabling direct observation and face-to-face interviews on site with zoo staff and zoo visitors. The findings of this research provide a snapshot of education communications offered to zoo visitors, and indicate that zoo exhibit signage remains the most prevalent medium. The findings further indicate that 95% of visitors read at least some exhibit signs and that more than 70% of participating zoos utilise person-to-person education. The implications of these findings for improving zoos' educational communication are discussed.